Distorsi Penggunaan Doktrin Business Judgment Rules dalam Putusan Nomor 121k/Pid.Sus/2020: (Perkara Tindak Pidana Korupsi Terkait PT Pertamina Hulu Energi dalam Kegiatan Investasi Blok BMG Australia) - Okky Rachmadi Soekristyanto; Khalimi Khalimi (Pusat Riset dan Inovasi Nasional, 2026)
This study examines the distortion between civil and criminal perspectives in the legal considerations (ratio decidendi) of Judex Juris in Supreme Court Decision Number 121K/Pid.Sus/2020. The decision lacks substantial criminal law considerations regarding the alleged corruption offense. Instead, the legal reasoning focuses on the fault or negligence of company directors, particularly the exception under Article 97 of Law Number 40 of 2007 concerning Limited Liability Companies, which embodies the Business Judgment Rule doctrine. Furthermore, these considerations are distorted by tort (onrechtmatige daad) as regulated in Article 1365 of the Civil Code juncto Article 138 paragraph (1) letter b of the Company Law. This research employs a legislative approach by analyzing various legal instruments, including the 1945 Constitution, the Criminal Code, the Criminal Procedure Code, the Limited Liability Company Law, State-Owned Enterprises Law, Judicial Power Law, Supreme Court Law, and the Corruption Eradication Laws. A conceptual approach is also utilized to examine theoretical concepts concerning corporate crime, directors' liabilities, state losses, tort, negligence from criminal and civil perspectives, business judgment rules, collective collegiality principles, and formal-material classification of legislation. The data comprises primary legal materials (legislation and court decisions) and secondary legal materials (legal literature and scientific journals). Analysis is conducted qualitatively by interpreting legal principles and their relevance to the court's considerations in the decision.